PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT. FAJAR AGUNG PHARINDO PROVINSI BANTEN (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
This research was conducted to determine the effect of Product Quality and Service Quality on Customer Satisfaction PT. Fajar Agung Pharindo, Banten Province. This type of research is explanatory, with the technique of collecting data through a questionnaire. The sampling technique used saturated sampling technique,the sample amounted to 80 people who are employees of PT. Fajar Agung Pharindo. The analytical method used in this research is quantitative data analysis.From the results of hypothesis testing shows that product quality has a positive and significant effect on customer satisfaction, service quality also has a positive and significant effect on customer satisfaction. The conclusion of this research is product quality and service quality have a positive and significant impact on customer satisfaction at PT. Fajar Agung Phrindo either partially or simultaneously.